Bu-Yin-Qian-Zheng Formula Ameliorates MPP+-Induced Mitochondrial Dysfunction in Parkinson’s Disease via Parkin - Ma, Hao-Jie; Gai, Cong; Chai, Yuan; Feng, Wan-Di; Cheng, Cui-Cui; Zhang, Jin-Kun; Zhang, Yu-Xin; Yang, Lu-Ping; Guo, Zhen-Yu; Gao, Yu-Shan; Sun, Hong-Mei (Frontiers in Pharmacology, 2020)
As a typical traditional Chinese medicine, Bu-Yin-Qian-Zheng Formula (BYQZF) has been shown to have neuroprotective effects in patients with Parkinson's disease (PD), particularly by ameliorating mitochondrial dysfunction and regulating expression of the parkin protein. However, the underlying mechanisms by which BYQZF affects mitochondrial function through parkin are unclear. Accordingly, in this study, we evaluated the mechanisms by which BYQZF ameliorates mitochondrial dysfunction through parkin in PD. We constructed a parkin-knockdown cell model and performed fluorescence microscopy to observe transfected SH-SY5Y cells. Quantitative real-time reverse transcription polymerase chain reaction and western blotting were conducted to detect the mRNA and protein expression levels of parkin. Additionally, we evaluated the cell survival rates, ATP levels, mitochondrial membrane potential (ΔΨm), mitochondrial morphology, parkin protein expression, PINK1 protein expression, and mitochondrial fusion and fission protein expression after treatment with MPP+ and BYQZF. Our results showed that cell survival rates, ATP levels, ΔΨm, mitochondrial morphology, parkin protein levels, PINK1 protein levels, and mitochondrial fusion protein levels were reduced after MPP+ treatment. In contrast, mitochondrial fission protein levels were increased after MPP+ treatment. Moreover, after transient transfection with a negative control plasmid, the above indices were significantly increased by BYQZF. However, there were no obvious differences in these indices after transient transfection with a parkin-knockdown plasmid. Our findings suggest that BYQZF has protective effects on mitochondrial function in MPP+-induced SH-SY5Y cells via parkin-dependent regulation of mitochondrial dynamics.